Unpacking Sources of Comparative Advantage: A Quantitative Approach - CHOR, Davin (Institutional Knowledge at Singapore Management University, 2008)
This paper develops an approach for quantifying the relative importance of different sources of comparative advantage for country welfare in a global trade equilibrium. To explain the pattern of specialization, I present a multi-country, perfectly-competitive Ricardian model that extends Eaton and Kortum (2002) to predict industry trade flows. In this framework, comparative advantage is determined by the interaction of country and industry characteristics, with countries specializing in industries whose specific production needs they are best able to meet with their factor endowments, institutional environment, and technological strengths. I estimate the model parameters using a large dataset of bilateral trade flows, comprising 82 countries and 20 manufacturing industries. I present results from a baseline OLS approach, and a simulated method of moments (SMM) procedure that takes into account the prevalence of zero trade flows in the data. The SMM estimates imply large average welfare gains from a hypothetical reduction in distance barriers, with developing countries benefiting substantially more than the OECD. I also examine the induced shift in industry composition when countries raise their factor endowments or improve the quality of their institutions, and quantify the welfare gains generated by such policy moves.